Management of rheumatology disorders and the pharmacist’s role: gout and related conditions - Ismail, Mohammad; Sajid, Hira; Khan, Fahadullah; Nik Mohamed, Mohamad Haniki (Elsevier, 2019)
Gout is the most common crystal-induced arthropathy that is associated with hyperuricemia and deposition of monosodium urate crystals in joints and soft tissues. Gout-related arthropathy results in functional impairment and poor health-related quality of life in many patients. This chapter describes different aspects of gout including its epidemiology, etiopathogenesis, and clinical manifestations. Various therapeutic approaches and their selection for the treatment of acute gout attack and hyperuricemia are discussed. Other crystal-induced arthropathies are briefly covered. The chapter also discusses the specialized roles of pharmacists including development of care plan, monitoring of therapy outcomes, patient education, and assessment/management of adverse drug effects and drug interactions.